Plasma urocortin in acute myocardial infarction patients - Arintaya Phrommintikul (2018)
Background Despite its proposed cardioprotective effect, the role of plasma urocortin in acute myocardial infarction (AMI) remains unknown. We investigated plasma profile of urocortin in AMI patients and evaluated its long-term prognostic performance. Material and methods Sixty-six AMI patients and 21 healthy subjects were included in this study. Blood samples for urocortin were collected on days 0 (onset), 1, 3 and 5 and at 3 and 6 months. Primary endpoint was mortality within 1 year of follow-up. Secondary endpoint was combined death and nonfatal adverse cardiac events (i.e. myocardial reinfarction, urgent revascularization or hospitalization due to heart failure) within 1 year. Results During follow-up at 1 year, 38 (57·6%) patients were alive without cardiac events, nine (13·6%) had nonfatal cardiac events and 17 (25·8%) died. Plasma urocortin in AMI patients were increased on days 0, 1, 3 and 5 (P < 0·05 vs. control). The receiver-operating characteristic curve showed an area under curve (AUC) of day 0 urocortin to be 0·750 with 95% confidence interval (CI) of 0·619-0·881 (P = 0·004), whereas AUC of NT-proBNP was 0·857 (95% CI, 0·722-0·992; P = 0·003). Sensitivity values for predicting the mortality of urocortin NT-proBNP and a combined urocortin and NT-proBNP were 0·81 (95% CI, 0·54-0·95), 0·86 (95% CI, 0·42-0·99) and 1·0 (95% CI, 0·56-1·0), respectively. Conclusions Plasma urocortin level is elevated in AMI patients for 5 days from onset. High plasma urocortin within 24 h after the onset is associated with increased mortality. Combined urocortin and NT-proBNP enhance prognostic performance in AMI patients. © 2010 Stichting European Society for Clinical Investigation Journal Foundation.